EMPOWERING LOCAL ECONOMIES INNOVATIVE APPROACHES TO GENDER-INCLUSIVE GOVERNANCE IN INDONESIAN REGIONS - Djamal, Mansyur; Nurhayati, Siti; Imran, Treesje; Hermansyah, Muhammad; Hasibuan, Masnilam (VISIONER : Jurnal Pemerintahan Daerah di Indonesia, 2024)
This study explores the impact of gender inclusion in public governance on local economic empowerment in Indonesia. The main focus of this study is to identify how women's representation in leadership positions and holistic gender inclusion policies affect economic well-being at the local level. The research methods used include quantitative analysis, namely Descriptive statistics analysis, Discriminant Validity (Farnell Larcker Criterion), Reliability Test, Path Analysis, and Research Hypothesis Testing. The results of the study indicate that gender inclusion in public governance has a significant positive impact on local economic empowerment. In addition, women's representation in leadership positions and comprehensive gender inclusion policies contribute more to economic growth than policies focusing on essential participation. Although these results support the theory of the benefits of gender inclusion, policy implementation faces obstacles such as cultural resistance and lack of resources. These findings suggest the need for a more integrated and sustainable approach to maximise the positive impact of gender inclusion policies.